The Implementation of Teaching-Learning Cycle in English for Hotels Training: A Case Study - Raden Arief Nugroho (ASIAN TEFL Journal of Language Teaching and Applied Linguistics, 2018)
Education and training are now integral elements for all sectors and agencies operating within tourism industry. However, despite the importance of training, many educators and trainers have entered the industry without a well structured tourism training method. The teaching-learning cycle consisting of Building Knowledge of Field, Modelling, Joint Construction, and Independent Construction which is used in our formal educational level can also be used to give well understanding tourism training, particularly in English for hotels training. This study aims to introduce those already working in the industry, particularly hotel employees, to the cycle aiming to improve the participants’ speaking performance in English for hotels. Fourteen participants were taking part in this training. In addition, there were fourteen meetings in this training and the final assessment was conducted in the final meeting. The data were collected through the assessment by using the Format of the Cambridge ESOL First Certificate in English (FCE) spoken language test in the last meeting. In addition, the collected data from the final assessment were compared to the collected data from the early assessment before the treatment had been conducted and the parameter of success was evaluated by using the Holistic Rating Scale and the Foreign Services Institute (FSI) Analytic Rating Scale. The result shows that in the last meeting participants were able to increase their speaking ability. The outcome shows that the participants were able to set their rating almost 1-2 level(s) higher. In addition, the study shows that training by using the teaching-learning cycle thrives to improve and motivate most of the participants to be brave to speak or pronouncing the words or sentences better.